Epistolary Labours: Reading Childbirth and the Politics of Reproductive Medicine in Two Eighteenth-Century Women’s Letters - Boon, Sonja (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
Birth stories, as numerous scholars have observed, are central aspects of maternal identity. Such stories build community, enabling women to navigate what Fiona Nelson (2009) has referred to as the “culture of motherhood.” In this essay, I offera detailed analysis of two eighteenth-century birth stories. I argue that these two narratives, both written by elite women during the second half of the eighteenth century, allow the contemporary reader a window not only into eighteenth-centuryexperiences of childbirth, but more importantly, into the tensions that sometimes arose between labouring women and the medical personnel who were meant to support them.